Marine resources effective in controlling and treating diabetes and its associated complications. (May 2020) - Nasab, Soudeh Bahramian; Homaei, Ahmad; Pletschke, Brett I.; Salinas-Salazar, Carmen; Castillo-Zacarias, Carlos; Parra-Saldívar, Roberto
Highlights: Natural compounds derived from marine resources effectively control and treat diabetes. The marine environment has proven to be a valuable resource against diabetes. The therapeutic mechanisms that affect diabetes and its complications are discussed. Abstract: Diabetes is a metabolic disorder characterized by a chronic increase in blood glucose. This disease is a major threat to public health and is one of the main causes of mortality in developed and developing countries. Despite the availability of a variety of antidiabetic drugs, the major constraints of these synthetic drugs - including high costs, efficacy and adverse effects - have led researchers to seek more effective alternative therapies with less costly side effects. In this study, we investigated different bioactive compounds in marine resources that may be potentially useful in treating or managing diabetes, as well as describe the various therapeutic mechanisms affecting diabetes and its complications, including inhibition of α-amylase, α-glucosidase, β -glucosidase, glycogen synthase kinase 3β (GSK-3β), lipase, aldose reductase, protein tyrosine phosphatases 1B (PTP1B) and dipeptidyl peptidase IV   (DPP-4), prevention of insulin resistance, increased phosphorylation of the AMP-activated protein kinase (AMPK) and adjusting the metabolism of glucose and lipids, stimulation of natural killer cells, anti-inflammatory effects, induction of liver antioxidant activity, reduction in oxidative stress and protection of β-pancreatic cells. This review focuses on the presentation of previous studies performed on a variety of potential marine resources against diabetes.